Nineteenth-Century Collective Violence: Toward a North American Context - See, Scott (Labour/Le Travailleur)

(untitled) (Canadian Committee on Labour History, 1997)
The study of collective violence has generally reinforced national stereotypes that Canada is a "Peaceable Kingdom" and that the United States is extraordinarily violent. This article assesses the historiography of collective violence since the1960s and offers specific suggestions for further exploration into Canada's riotous experiences. Scholars often assume that Canada's collective violence has been infrequent and less destructive than American episodes. Future research — with a focus on nativism, the social legitimacy of the crowd, religious and ethnic conflict, the entrenchment of powerful state institutions, and vigilantism —might prove otherwise. Regardless, Canadian collective violence will be better understood if it is conceptualized in a North Atlantic context